Antenna Beamwidths of Above-The-Road Radar for Traffic Speed Enforcement in China. (1st August 2012) - Du, Lei; Sun, Qiao; Cai, Changqing; Zhang, Yue; Hu, Hongbo
Abstract : Above-The-Road (AbTR) radar is a new type of speed measurement device used in China for traffic speed enforcement. The antenna beamwidths in vertical and horizontal directions are critical parameters for AbTR radar because speed measurement accuracy partly depends on vertical beamwidth and speed measurement interference from adjacent lanes can be effectively minimized by appropriate choice of horizontal beamwidth. In this paper, the speed measurement principle of AbTR radar is introduced and the reason for field speed measurement error is presented. The speed measurement error is theoretically calculated in various combinations of different vertical beamwidths and possible installation angles. The requirement for horizontal beamwidth to operate with less interference from adjacent lanes is also theoretically laid down with different installation heights and angles. Field tests with three equal-distanced piezosensors each lane as triggering references have been performed on an AbTR radar sample with vertical beamwidth 5.1° and horizontal beamwidth 5.2°. The results of theoretical analysis and field tests validate that the requirement of less than 6° for AbTR radar antenna beamwidths in vertical and horizontal directions is a precondition for accurate and reliable field measurements, which has been added to the China's pattern approval regulation for AbTR radar devices newly published.